This preview shows page 1. Sign up to view the full content.
Unformatted text preview: s and t are both odd and ( s, t ) = 1 then ( st, s + t ) = 2. (Hint: Refer to Question 2 from HW set 2.) Step 4. If x, y are both odd, assume ( x, y ) = 1 and show that x 2 + y 2 = 2 a 2 , x + y = 2 b 2 , xy = 2 c 2 for some a, b, c ; hence, a 2 = b 4 + c 4 . Step 5. If x, y are both even, assume x = 2 x and y = 2 y with ( x , y ) = 1. Use Step 3 to show that x 2 + y 2 = 8 a 2 , x + y = 4 b 2 , xy = 4 c 2 for some a, b, c ; hence, a 2 = b 4 + c 4 . Step 6. Use the theorem that the equation x 4 + y 4 = z 2 has no solutions. 1...
View
Full
Document
 Spring '08
 YEE
 Number Theory, Angles, Integers

Click to edit the document details